A Study on Squatter Settlements of Kathmandu Using GIS, Aerial Photography, Remote Sensing and Household Survey - K.C., Kiran; Pahari, Krishna (Journal on Geoinformatics, Nepal, 2011)
The study was done to explore various issues facing by the squat dwellers of two densely populated squatter settlements of the Kathmandu valley (Manohara and Thapathali). A series of temporal satellite imageries along with orthophoto were analyzed and mapped focusing the food security and their livelihood conditions, sanitary and hygienic conditions and the flood hazard assessment. The study revealed that there has been a drastic landuse change in the Manohara area as compared to the Thapathali one. The squatter settlement that currently exists is found to have been in the flood plain. The household survey has disclosed that a majority of squatters who have settled in these places belong to Janajatis and they have mainly migrated from the hilly region and the surrounding districts of the Kathmandu valley. Besides, drinking water tested from both of the areas is contaminated with high concentration of Nitrate and Coliform. Hygienic conditions are also very poor as toilets lie along the river banks resulting in the depletion of the river quality and the scenic beauty of the surrounding environment. The community-based flood hazard mapping done with the GPS survey has revealed that all the settlements from both of the areas had been inundated in the month of July in 2009. In both area, people are deprived of basis amenities and they have been neglected by the concerned government authorities. Adequate research on scientific basic is an urgent need so as to draft a clear cut specific policy that can address their issues and stop environmental deterioration, destruction of beautiful green grassland and the sanitary conditions.